Implementation Of PBL Model To Enhance Critical Thinking Skills And Argumentation Skills Of Students - Indra Drajat Sopwan; Usep Soetisna; Sri Redjeki (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2018)
This research is the tendency of students who only received learning material sourced from teachers through lectures, so that students are less active in the learning process more towards teacher centered. Because during the learning process in the classroom only emphasize knowledge of low-level thinking, students should be able to develop the ability of critical thinking and argumentation skills of students during the learning process so that it will get used to argue and higher level thinking. This study aimed to analyze the implementation of PBL models to improve the ability of critical thinking and argumentation skills as well as to determine the relationship between the ability of critical thinking skills and argumentation skills. The method used Nonequivalent Control Group Design. The population in this study is the class X.1 and X.2 Senior High School PGRI 1 Majalengka in 2015/2016 school year and totaling 47 students. Sampling was done by using cluster random sampling, were divided into 2 groups: PBL model class with 24 students and other class are not using PBL as many as 23 students. Instruments in this research is the description of critical thinking skills and argumentation skills test, observation sheets and questionnaires for students. Hypothesis test using parametric statistical tests in this case to test the hypothesis of implementation PBL models to enhance the critical thinking skills using Manova test was obtained p 0.05 is 0.01 0.05, which means there is an increased implementation of the PBL model of critical thinking skills of students and hypothesis test of  implementation PBL model to enhance argumentation skills of was obtained p 0.05 is 0.03 0.05, which means there is an increased implementation of the PBL model of argumentation skills of the students, as well as the correlation coefficient to determine the relationship of critical thinking skills and the skills of argumentation studied through the PBL model obtained p 0.05 is 0.049, which means there is an interaction between critical thinking skills and argumentation skillsKeywords: PBL Model; Critical Thinking Skills; Argument Skills